Influence of gamma irradiation on microflora, sensory quality, nutritional properties and shelf life of Desi chickpea (Cicer arietinum) - Abdullah, Roheena; Zulfiqar, Mubshra; Akram, Zainab; Iqtedar, Mehwish; Kaleem, Afshan; Naz, Shagufta (Progress in Nutrition, 2018)
Chickpea is one of the highly nutritious pulses. It is a rich source of proteins and carbohydrates, providing dietary as well as health benefits too. Pakistan is the 3rd major producer, of chickpea but due to post harvest losses (insect and microbial infestation) huge quantity of Desi chick pea goes to waste. In the present study, the research was directed to increase the shelf life by reducing post-harvest losses of Desi chickpea using gamma radiations. The Desi chick pea were irradiated at different gamma radiation doses (0.5, 1, 2 kGy). Sensory analysis, insect infestation, proximate and microbial analysis were carried out after every 20 days interval for all the treatments. A remarkable reduction in microflora and insect infestation was occurred at 2kGy as compared to control samples stored at ambient temperature without affecting the sensory properties. The variation in proximate composition with gamma radiation treatment was not significant with increase in dose. Sample irradiated at 2kGy showed one month shelf life enhancement as compared to control.